Towards a better understanding of metal nanoparticles, a novel strategy from eucalyptus plant - Hanadi, Sawalha; Abiri, Rambod; Sanusi, Ruzana; Shaharuddin, Noor Azmi; Mohamad Noor, Aida Atiqah; Ab Shukor, Nor Aini; Abdul Hamid, Hazandy; Ahmad, Siti Aqlima (Multidisciplinary Digital Publishing Institute, 2021)
Nanotechnology is a promising tool that has opened the doors of improvement to the quality of human’s lives through its potential in numerous technological aspects. Green chemistry of nanoscale materials (1–100 nm) is as an effective and sustainable strategy to manufacture homogeneous nanoparticles (NPs) with unique properties, thus making the synthesis of green NPs, especially metal nanoparticles (MNPs), the scientist’s core theme. Researchers have tested different organisms to manufacture MNPs and the results of experiments confirmed that plants tend to be the ideal candidate amongst all entities and are suitable to synthesize a wide variety of MNPs. Natural and cultivated Eucalyptus forests are among woody plants used for landscape beautification and as forest products. The present review has been written to reflect the efficacious role of Eucalyptus in the synthesis of MNPs. To better understand this, the route of extracting MNPs from plants, in general, and Eucalyptus, in particular, are discussed. Furthermore, the crucial factors influencing the process of MNP synthesis from Eucalyptus as well as their characterization and recent applications are highlighted. Information gathered in this review is useful to build a basis for new prospective research ideas on how to exploit this woody species in the production of MNPs. Nevertheless, there is a necessity to feed the scientific field with further investigations on wider applications of Eucalyptus-derived MNPs.